Comparing the driving behaviours of individuals with frontotemporal lobar degeneration and those with Alzheimer's disease. Issue 1 (3rd March 2015) - Fujito, Ryoko; Kamimura, Naoto; Ikeda, Manabu; Koyama, Asuka; Shimodera, Shinji; Morinobu, Shigeru; Inoue, Shimpei
Abstract: Background: Assessing driving aptitude in dementia patients is critically important for both patient and public safety. However, there have been only a few reports on the driving behaviours and accident risk of patients with dementia, especially frontotemporal lobar degeneration (FTLD). Therefore, we compared the characteristics of driving behaviours in patients with FTLD and those with Alzheimer's disease (AD). Methods: The subjects were 28 FTLD and 67 AD patients who visited the Department of Psychiatry, Kochi Medical School Hospital. We conducted semi‐structured interviews with their families and caregivers about traffic accident history and changes in patient driving behaviours after dementia onset and then compared the findings between the two groups. Results: Overall changes in driving behaviours were reported in 89% (25/28) and 76% (51/67) of the FTLD and AD patients, respectively ( P = 0.17). In the FTLD group, difficulty in judging inter‐vehicle distances, ignoring road signs and traffic signals, and distraction were reported in 50% (14/28), 61% (17/28), and 50% (14/28) of patients, respectively, and 75% (21/28) patients had caused a traffic accident after dementia onset. The risk of causing an accident was higher in the FTLD group than in the AD group (odds ratio = 10.4, 95% confidence interval = 3.7–29.1). In addition, the mean duration between dementia onset and a traffic accident was 1.35 years in the FTLD group compared with 3.0 years in the AD group ( P < 0.01). Conclusions: Patients with FTLD were more likely to show dangerous driving behaviours than those with AD, and the risk of causing a traffic accident may be higher in patients with FTLD from an early disease stage.